2010
DOI: 10.1148/radiol.09081546
|View full text |Cite
|
Sign up to set email alerts
|

Combined Pulmonary Fibrosis and Emphysema: 3D Time-resolved MR Angiographic Evaluation of Pulmonary Arterial Mean Transit Time and Time to Peak Enhancement

Abstract: Purpose:To correlate conventional invasive pressure indexes of pulmonary circulation with pulmonary fi rst-order arterial mean transit time (MTT) and time to peak enhancement (TTP) measured by means of three-dimensional timeresolved magnetic resonance (MR) angiography in patients with combined pulmonary fi brosis and emphysema (CPFE). Materials and Methods:The study was institutional review board approved. All subjects involved in the study provided written informed consent. Eighteen patients with CPFE were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 37 publications
1
30
0
4
Order By: Relevance
“…Studies from COTTIN and co-workers [44,45] and SERGIACOMI et al [46] identified combined pulmonary fibrosis and emphysema (CPFE) as a relevant clinical entity, as mean survival is shorter than in other forms of IIP, the incidence of pulmonary hypertension is higher and PFTs are potentially confounding. Although CE was not an independent prognostic factor, our study showed that, in the long term, patients with CE have a worse prognosis than those without CE.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from COTTIN and co-workers [44,45] and SERGIACOMI et al [46] identified combined pulmonary fibrosis and emphysema (CPFE) as a relevant clinical entity, as mean survival is shorter than in other forms of IIP, the incidence of pulmonary hypertension is higher and PFTs are potentially confounding. Although CE was not an independent prognostic factor, our study showed that, in the long term, patients with CE have a worse prognosis than those without CE.…”
Section: Discussionmentioning
confidence: 99%
“…MRI perfusion imaging can provide information about the presence of perfusion defects at higher spatial resolution than perfusion scintigraphy. These functional haemodynamic-sensitive MR techniques have the potential to quantify the pulmonary blood flow and regional pulmonary vascular resistance and predict the surgical outcome [20,21]. The presence of dilated bronchial arteries has been shown to correlate with a lower mortality rate after pulmonary thrombo-endarterectomy and CE-MRA has been shown to accurately estimate the flow in the bronchial arteries in patients with CTEPH [22].…”
Section: Discussionmentioning
confidence: 99%
“…PBF has been shown to improve in CTEPH patients who have had pulmonary endarterectomy (40). There is also an increase in MTT in patients with pulmonary arterial hypertension (PAH), which shows a modest correlation with mPAP (41,42) and in patients with combined emphysema and fibrosis MTT correlates with mean pulmonary artery pressure and pulmonary vascular resistance (43). In addition, in patients with PAH, pulmonary transit times have been shown to correlate with markers of disease severity, mean right atrial pressure and pulmonary vascular resistance (44) and are predictive of mortality at univariate analysis and have equivalent prognostic value to invasive measures taken at right heart catheterisation (45).…”
Section: Clinical Applications Of Pulmonary Mra and Perfusion Imagingmentioning
confidence: 99%